Feasibility of Investing in Carbon Efficient Equity Portfolios - Singh, Ranjit; Leepsa, N. M. (Universiti Utara Malaysia Press, 2016)
The paper investigates the returns and risk given by the carbon efficient equity indices in India, USA, Japan, and Brazil, and compares them with that of their corresponding benchmark market indices. Data with respect to the considered indices were collected from the official websites of the respective stock exchanges. It was found that there was no difference in the return and risk given by the carbon efficient equity indices with that of their benchmark market indices.There was also no substantial difference with respect to the return generated by the carbon efficient equity indices among the four countries. This study is first of its kind and hence original in nature.